Effect of different baits on the catch performance of bottom longline in the kampar river, Sendayan Village, Riau - Muhammad Hafit; Inaniah Inaniah; Riska Fatmawati (Universitas Teuku Umar, 2026)
Bottom longline is one of the traditional fishing gears widely used by fishermen in river waters, including in the Kampar River, and its effectiveness is greatly influenced by the type of bait used. This study aims to analyze the effect of different bait types on the catch of bottom longline in the Kampar River, Sendayan Village, Riau Province. The baits tested were paweh fish (Osteochilus hasselti) and siban fish (Cyclocheilichthys apogon), two local fish species commonly used by local fishermen. The method employed was experimental fishing conducted over seven days with two operations per day. The parameters observed included the number of individuals and the total weight of the catch. The results showed that the use of siban fish as bait produced significantly higher catches than those with paweh fish (p < 0.05). This study provides a scientific basis for fishermen to select a more effective, efficient, and sustainable bait type to enhance the productivity of bottom longline fishing gear in the waters of the Kampar River.